Coupling kinetic Monte Carlo and finite element methods to model the strain path sensitivity of the isothermal stress-assisted martensite nucleation in TRIP-assisted steels. (March 2021) - Cluff, Stephen; Knezevic, Marko; Miles, Michael P.; Fullwood, David T.; Mishra, Raja K.; Sachdev, Anil K.; Brown, Tyson; Homer, Eric R.
Abstract: The properties of TRIP-assisted steels are influenced by the transformation of retained austenite into martensite during deformation via the mechanically-induced martensite transformation. In the present work the effect of strain path on isothermal stress-assisted martensite nucleation and variant selection are studied by the coupling of the kinetic Monte Carlo method with the finite element method. This coupled model centers on a thermomechanical model of the martensitic transformation, and the model is tuned and validated against transformation data gathered experimentally for a TRIP-assisted dual phase steel (Ennis et al. (2017)). The effect of the proximity of adjacently transforming regions (kinematic coupling) is also studied as a function of strain path. The model results demonstrate how the rate of martensite nucleation is affected by the strain path (uniaxial tension, biaxial tension, and plane strain) and how the kinematic coupling between adjacent transforming regions is unique to each path. These phenomena are discussed in the context of the Magee effect, which is the relationship between stress state and the suppression/assistance of the nucleation of specific variants of martensite. The implications of martensite nucleation's sensitivity to strain path and kinematic coupling are discussed for TRIP-assisted steels that transform by isothermal stress-assisted nucleation. Graphical abstract: Highlights: Model simulates kinetics of martensite nucleation by coupling KMC method with FEA. Model validated by transformation data from TADP steel, which is TRIP-assisted. Martensite nucleation kinetics are affected by strain path and kinematic coupling. The Magee effect underlies differences in nucleation kinetics between load paths. Plane strain is most sensitive to kinematic coupling.